2007
DOI: 10.1128/ec.00229-06
|View full text |Cite
|
Sign up to set email alerts
|

Coding Tandem Repeats Generate Diversity in Aspergillus fumigatus Genes

Abstract: Genes containing multiple coding mini-and microsatellite repeats are highly dynamic components of genomes. Frequent recombination events within these tandem repeats lead to changes in repeat numbers, which in turn alters the amino acid sequence of the corresponding protein. In bacteria and yeasts, the expansion of such coding repeats in cell wall proteins is associated with alterations in immunogenicity, adhesion, and pathogenesis. We hypothesized that identification of repeat-containing putative cell wall pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 42 publications
7
115
0
Order By: Relevance
“…Potential mechanisms for deletion or insertion of the tandem repeats include slipped-strand mispairing, unequal crossover, rolling-circle or circle excision, and reinsertion occurring during bacterial replication (30,39). This size variation caused by different numbers of tandem repeats provides the opportunity for functional diversity and alterations in phenotypes (20,29,48). Although the functions of hyv I and hyv II genes are unknown, BLASTP analysis using positionspecific iterative basic local alignment search tool (PSI-BLAST) indicated that the repeat region of Hyv I protein shares homology with a leucine-rich repeat protein, cell wallassociated biofilm protein, and a cell surface protein.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms for deletion or insertion of the tandem repeats include slipped-strand mispairing, unequal crossover, rolling-circle or circle excision, and reinsertion occurring during bacterial replication (30,39). This size variation caused by different numbers of tandem repeats provides the opportunity for functional diversity and alterations in phenotypes (20,29,48). Although the functions of hyv I and hyv II genes are unknown, BLASTP analysis using positionspecific iterative basic local alignment search tool (PSI-BLAST) indicated that the repeat region of Hyv I protein shares homology with a leucine-rich repeat protein, cell wallassociated biofilm protein, and a cell surface protein.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 3% of these minisatellites are located in genes that encode potential cell surface proteins. One of these genes (Afu3g08990) was inactivated and the corresponding mutant conidia showed decreased cellular adhesion, although no effect on virulence in a mouse model was detected (279).…”
Section: Vol 72 2008 Dna Repeats In Eukaryotes 695mentioning
confidence: 99%
“…Although numerous papers were published recently on the application of several typing techniques to A. fumigatus isolates, only some authors attempted to examine the reproductive mode of A. fumigatus populations and the conclusions drawn by them were controversial (Girardin et al 1994, Fridkin & Jarvis 1996, Lasker 2002, Levdansky et al 2007. In Latin America, there is very little information on these different aspects of the epidemiology of aspergillosis.…”
mentioning
confidence: 99%